Vitamin D levels in patients with recurrent aphthous stomatitis - Aynure Öztekin; Coşkun Öztekin (BMC, 2018)
Abstract Background Lower serum vitamin D levels, a major public health problem worldwide, has been found to be associated with various infectious diseases, cancers, autoimmune and dermatological diseases. The serum levels of vitamin D in patients with recurrent aphthous stomatitis are not clear. We investigated the vitamin D levels in patients with recurrent aphthous stomatitis. Methods Forty patients with recurrent aphthous stomatitis (Group I) and 70 healthy controls (Group II) included in the study. The characteristics of aphthous lesions (duration of disease and remission, frequency, diameter and number of the lesions) and demographics of the participants were recorded. Serum 25-hydroxycholecalciferol levels were measured using electrochemiluminescence binding method. Results There was no statistically significant difference between the groups in terms of age (p = 0.06) and sex (p = 0.4). Other baseline characteristics were not significantly different between the groups (p > 0.05 for all). The mean diameter of aphthous lesions was 0.5 (0.4-0.6) cm and the mean number of lesions was 2.2 ± 1.5. Serum vitamin D levels were 11 ± 7.04 ng/ml in Group I and 16.4 ± 10.19 ng/ml in Group II. Serum vitamin D levels were significantly lower in patients with recurrent aphthous stomatitis (p = 0.004). Conclusions The present study showed lower vitamin D levels in patients with recurrent aphthous stomatitis compared to healthy controls.